An analog electronic emulator of non-linear dynamics in optical microring resonators. (December 2021) - Minati, Ludovico; Mancinelli, Mattia; Frasca, Mattia; Bettotti, Paolo; Pavesi, Lorenzo
Highlights: An analog electronic emulator of self-pulsing in optical microresonators is designed. Its response to pump amplitude and detuning tracks optical recordings and simulations. The qualitative features of free carrier and thermo optic phenomena are reproduced. The possibility of coupling is demonstrated, enabling future network construction. Abstract: The microring resonator is a ubiquitous building block of optical integrated circuits. Owing to its unique non-linear properties, it appears well-suited as a node in the realization of photonic networks, such as spiking neural networks. However, experimental investigation requires complex setups, incurring considerable device fabrication times and costs. Inherent physical constraints limit the ranges of the parameters determining the timescales and strengths of the non-linear behaviors. Moreover, on-the-fly changes to these parameters and node couplings are not easily realizable. On the other hand, numerical simulations are computationally heavy, particularly for large networks, and do not entirely replace measurement on a physical apparatus. To mitigate this problem, we introduce and realize an analog electronic emulator that implements dynamics, attempting to reproduce the self-pulsing phenomenon in an optical microresonator. It can be readily constructed with off-the-shelf components, and is well-suited for building complex networks. The circuit is explicitly based on a mathematical model of the microresonator, subject to some approximations, parameter adjustments and rescalings. Initial results comparing experimental data from the emulator and a representative silicon photonic device plus numerical simulations suggest a satisfactory level of agreement in the temporal dynamics and response to parametric sweeps when scaled for the different response times. This work exemplifies the relevance of explicitly establishing correspondences between physical systems having widely different features but governed by similar dynamics.